Sublime Innocence of Human Soul: Reanalysing Traherne's Deep Philosophical Optimism of the Divine Verses - Shantanu Siuli (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
This paper aims to demonstrate a crucial observation of Thomas Traherne's philosophical optimistic approach of reshaping and reviving the true self of the soul's projection towards salvation through enormous and steadfast devotion to God. Traherne's fundamental optimistic outlook on the notion of the sacrament and spiritual sense made a fitting and realistic undertone towards the changing scenario of divinity and the concept of devotion during seventeenth-century England. Traherne's philosophical optimistic approach towards divinity is a strong propensity of rekindling the effects of the seventeenth-century devotion to God and led that matter very clear and evocative to the susceptibility of the divine impulse of humankind. Traherne is and will be discussed nowadays, why he will be given the privilege, and what significance his work bears is a matter of ongoing critical judgment. Unhesitatingly the fact relating to Traherne's overall justification and outlook to the divinity and sacramental identity of his time, must be acknowledged that he was a mystic not by compulsion or having no other option to do, but by choice completely derived from heart, which was also palpitating, unlike other human beings who wanted to be devout sincerely, vivifying its own identity towards God.